From the dead - Billingham, Mark (Billingham, Mark. DI Tom Thorne series ;, 2014)
"In the gripping ninth Tom Thorne novel, a man long thought killed by his long-suffering wife turns up alive. And other people begin to turn up dead. A decade ago, Alan Langford's charred remains were discovered in his burnt-out car. His wife, Donna, was found guilty of conspiracy to murder her husband and sentenced to ten years in prison. But before she is released, Donna receives a nasty shock: an anonymous letter containing a photo of her husband. The man she hates with every fiber of her being-- the man she paid to have murdered-- seems very much alive and well. But how is it possible that her husband is still alive? Where is he? Who sent the photo, and why?" --